PEMBAHARUAN PEMIKIRAN ISLAM SEBAGAI MANIFESTASI NILAI KETAUHIDAN - Abdillah, Abdillah (AL-Fikr, 2015)
This article discusses the renewal of Islamic thought as a manifestation of the values of monotheism. Tawhid is central and very fundamental concept in Islam. Undoubtedly the essence of Islam itself is an affirmation of monotheism-or acknowledgment that God is Almighty, Creator of absolute and transcendent, as well as King and Lord of the universe. Tawhid Islamic civilization is functionally or structural elements of civilization identity provider. Tawhid binding or integrating the entire basic elements so as to form a coherent whole, which is known as civilization. In the process of integrating the different elements of the essence of civilization-in this case typically forms tauhid- coloring. The authors came to the conclusion that the fundamental purpose of the renewal of Islamic thought in the religious life is to make the evolution of life is moving in a direction to move much more important for the purpose of ego than the moral health of the social structure that forms the current environment